O sofrimento psíquico de trabalhadores em situação de desemprego em Porto Velho - RO - Schlindwein, Vanderléia de Lurdes Dal Castel (2021)
The objective of this study was to analyze the psychic suffering of workers in unemployment situations attended by the National System of Employee - SINE Municipal of Porto Velho - RO. It is a quantitative, descriptive and cross-sectional survey with 50 unemployed workers. A sociodemographic interview and the Self-Reporting Questionnaire (SRQ-20) were applied. The study was approved by the Research Ethics Committee of the institution. The sample consisted of 60% male and 40% female, 14% of them were more than a year without work and 84% were making "beaks". The prevalence of common mental disorder (CMD) was found in 50% of the workers, 75% had depressed / anxious moods, 52% showed a decrease in vital energy, 35% had somatic symptoms and 34% had depressive thoughts. The results demonstrate a high prevalence of TMC and depressive, anxious and somatoform symptoms among unemployed workers in the SINE. It is concluded that it is important to direct actions of prevention and coping with the health care of workers in the state.